PWE-440 Trainee endoscopic procedures by deanery and grade in the united kingdom: september 2013 – august 2014. have we improved?. (22nd June 2015) - Bhatt, S; Ambrose, T; Dunckley, P; Ellis, A
Abstract : Introduction: In 2012 we demonstrated that UK Gastroenterology trainees were not meeting nationally agreed targets for endoscopic numbers, with variation both within and between deaneries. 1 These results were presented at a meeting of the Specialist Advisory Committee (SAC) in early 2013 and a discussion held about improving training. We repeated the analysis in 2014 looking for evidence of change. Method: Anonymised retrospective data for a 12 month period from September 2013 – August 2014 was collected from the Joint Advisory Group Endoscopic Training System (JETS) database. Only diagnostic procedures performed by gastroenterology trainees were included. Procedure numbers for diagnostic oesophago-gastro-duodenoscopy (OGD), flexible sigmoidoscopy and colonoscopy as well as numbers of dedicated training lists were analysed according to deanery and training grade. Mean, median, standard deviation and ranges were calculated. Endoscopic units (OGD/flexi =1; colon =2) were also calculated. Results were compared to the previous dataset. Results: 126, 448 procedures performed by 577 gastroenterology trainees in the 19 UK deaneries were identified. 72 (12%) of trainees were ST3, 110 (19%) ST4, 116 (20%) ST5, 120 (21%) ST6, 142 (25%) ST7 and 17 (3%) LAT. Median annual endoscopic units were lowest at ST3 and LAT grade. There was evidence of an increase at ST3, ST4, ST7 and LAT since 2012. There was marked variation in median annual procedures across the deaneries, as in 2012. Only 17% of trainees met nationally recommended numbers of diagnostic endoscopic procedures per annum set by the SAC. Adherence to targets for OGD were particularly poor in the ST4–ST7 cohort with 7–9% compliance. In the same cohort adherence to colonoscopy targets was between 28–39%. The median number of dedicated training lists per annum varied widely between deaneries with a range of 3–30 and a standard deviation of 7 (median = 18; mean = 17). Conclusion: This analysis corroborates our previous finding of a low adherence to recommended endoscopy numbers amongst gastroenterology trainees when compared to national standards. This data confirms widely held concerns amongst trainees and trainers. The data will be presented to training programme directors for discussion at a forthcoming SAC meeting. While competence is already assured through JAG assessments, improvements are still needed to ensure that those completing training are also confident endoscopists. Disclosure of interest: None Declared. Reference: Ambrose T, Dunckley P, Ellis AJ. Trainee endoscopic procedures by deanery and year of training in the United Kingdom: August 2011-July 2012. Are we doing enough? Gut 2013;62 :A47–A48